Problems And Solutions In Creating Works In The Landscape Genre (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article teaches how to create a fantasy world through works of the landscape genre, to be aware of shapes and colors, to be aware of the distance between the objects depicted in the landscape, the proportions and the relationship of colors to each other.